Wordsworth as an interpreter of nature - Ulrich, Dovie May (My University, 1903)
Introduction: INTRODUCTION. WHAT CONSTITUTES A NATURE POET. A nature poet is a poet who finds inspiration and material for his poetry in nature. He must love nature and understand it in all its moods. He must also see God’s love in nature. Every flower has for him a special message. He finds enjoyment in listening to nature’s voices and studying nature’s secrets. He would do as Bryant suggests— “Go forth under the open sky and list to nature’s teaching.” The poems of the nature poet must have something in nature for the theme. He must see in nature so much of truth, of beauty, of goodness, of love, of inspiration to righteousness – in a word, so much of the divine, that he is moved to glorify the commonplace, because he himself is uplifted into the realm of the spiritual and ennobled to “see the things that are invisible.” The nature poet must also be able to apply the lessons he receives from nature to life; he must be sympathetic with and love his countrymen and all humanity more, because of his insight into the works of creation. His poems should uplift humanity. He should tell others the beauties he finds in the visible universe and show them how to cultivate a love and appreciation for the world in which they live. Such a poet cannot be narrow and selfish. Otherwise he does not understand nature perfectly. Of course the nature poet must possess the requisites of a true poet with the love and comprehension of nature added. He must have, for example, imagination, without which he cannot draw a true picture of a landscape, a sunset, or a scene in the woods.
Citation: Ulrich, Dovie May. Wordsworth as an interpreter of nature. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Location of nursery; Preparation of Ground; Propagation of stock; Cultivation; Pruning; Digging; Storing; Shipment; Theses